Petrographic and geochemical characteristics of the Nui Chua pegmatoid mafic-ultramafic series, Northern Vietnam: Significance in petrogenesis and Fe-Ti-V metallogenesis - Dung, Pham Thi; Anh, Tran Tuan; Hung, Tran Quoc; Hoa, Tran Trong; Shelepaev, R. A.; Hoang, Nguyen; Cong, Tran Quoc (Vietnam Journal of Earth Sciences, 2020)
The pegmatoid intrusions of the Nui Chua complex are one of the important mafic-ultramafic intrusive series associated with Fe-Ti-V ores in northern Vietnam. These intrusions consist of plagiowebsterite, clinopyroxenite, melanogabbronorite, mesogabbro, gabbronorite, and leucogabbronorite. The Fe-Ti oxide ores being massive or disseminated appear layered or veined in pegmatoid rocks. The geochemical characteristics of pegmatoid rocks are rich in Fe, Ti, V and poor Mg; their HREE are higher than LREE, with [La/Yb]N of 0.49 to 0.91 (average: 0.67), showing negative anomalies at Nb, Ta, Th, U, Sr, Zr and positive anomalies at Cs, Ti, and K. The chemical composition and distribution characteristics of trace and rare earth elements of mafic and ultramafic rocks show that they share the same magma source. Having the same geochemical tendency of intrusive formations, Fe-Ti oxide ores are magmatic origin associated with intrusive pegmatoid rocks. The pegmatoid rocks of the Nui Chua complex and Fe-Ti oxide ores are formed as a product of the fractional crystallization of Fe-Ti-rich residual melts after crystallization of the layered rocks.